Uncombable hair: A condition with autosomal dominant inheritance. Issue 9 (September 1982) - Garty, B; Metzker, A; Mimouni, M; Varsano, I
Abstract : Uncombable hair is a familial abnormality of scalp hair structure which affects children and lessens as they grow older. It is suggested that the mode of inheritance of the condition is autosomal dominant.